Differences in Counseling Using Leaflets with Videos On Perineal Wound Treatment - Astutik, Reni Yuli; Purwandari, Eka Sri (Universitas Negeri Semarang cooperate with Association of Indonesian Public Health Experts (Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI)), 2021)
Background: Perineal wound needs to be treated to prevent infection, so postpartum needs counseling about perineal wound care. The perineal wound healing can be identified if the wound is dry, skin has been fused, not palpable and painless. This research aims to determine the different of counseling using leaflet with video toward perineal wound care behavior in primipara postpartumMethods: Quasi experiment with pre test and post test control group design. Pre test was conducted on the first day of the post partum, post test on the 7th day when the respondent controls the perineum wound. Instrument in this research used questionnaire regarding the behavior of perineal wound care. Samples in the research of a number of 30 people were taken in purposive sampling. Data analysis used the independent T test.Results: There were significant difference in counseling using leaflets and videos about the behavior of perineum wound care. The group that received perineal wound care counseling using video was better (p=0.015) than the leaflet group (p=0.034).Conclusions: Counseling about perineal wound care used videos more effective than leaflets.